Sonochemistry : applications and developments - Mason, Timothy J.; Vinatoru, Mircea (Berlin : De Gruyter, 2023)
Volume 2 contains six chapters which detail the developments of sonochemistry in fields which continue to attract considerable research and development interest from academia and industry. The topics range from the important developments in chemical synthesis through food technology and materials processing to therapeutic ultrasound. The authors have made contributions to all of these and so the content is written in a way which should be understandable to readers whose expertise may not necessarily be in the individual topic. Each of the applications and developments described help to illustrate not only the diverse nature of sonochemistry but also the unifying theme of the effects of acoustic cavitation on a wide range of procedures.
Includes index.
Keywords: Sonochemical synthesis -- Ultrasound waves -- Therapeutic ultrasound